Diagnosis and Management of a Unique Iatrogenic Biatrial Gerbode Defect. (18th July 2022) - Shuaib, Karim; Scorsese, Giacomo; Seiter, Christopher; Zabirowicz, Eric; Poppers, Jeremy
Abstract : The Gerbode defect was first described in the late 1950s as a congenital peri-membranous ventricular septal defect (VSD), resulting in a left to right ventriculoatrial shunt. We present a case of a patient with restenosis of a prior bioprosthetic aortic valve (AV) who underwent reoperative AV replacement (AVR), which was complicated by a unique iatrogenic Gerbode defect with concurrent LV-LA communication. Our case highlights the unique complications resulting from ventriculoatrial shunts, with consideration paid to the management of ventriculoatrial defects described.